Node Attestation for Reliable Communication in WSN - Kaur, Ranjit; Bansal, Khushboo (International Journal of Computer Sciences and Engineering, 2025)
A wireless sensor network is a group of specialized transducers with a communications infrastructure for monitoring and recording conditions at diverse locations. In this paper various approaches were described that were used for WSN. Leach is used in wireless sensor network and multi-hop leach protocol is used for energy consumed in a single hop for defining energy consumed in a single hop .By receiving various protocols the conclusion occur that leach is best protocol for WSN.